The Effect of The Supervision of The Principal and The Professional Competency of Teachers on Teacher Performance in Private MI in Pacet District - Ahmad Karim; Ari Kartiko; Dicky Edwar Daulay; Ika Dewi Kumalasari (Program Studi Manajemen Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2021)
In an institution or school, every teacher or teacher has a very important role in determining success in education. Therefore, teachers at least have pedagogic competence, professional competence, social competence and pedagogic competence. Given the importance of the role of the principal teacher as well as helping in solving problems or obstacles experienced by teachers, principals can also carry out supervision so that they know how the results of each teacher's assessment are. Supervision is a coaching activity planned to assist teachers and other school staff in carrying out their work effectively. Not only supervision, but the professional competence of teachers is no less important in helping teachers or in improving teacher performance. Professional competence itself means the ability to master the learning material broadly and deeply. In every institution certainly wants the best for the progress of the institution, principals and teachers must also have made efforts to improve performance. Therefore, it is necessary to pay special attention to the supervision of the principal and the professional competence of teachers, because both are very influential in improving teacher performance.